Correlations between biogas and dissolved methane generated and physical-chemical parameters of sewage in modified full-scale UASB-type reactors - Patulski, Ana Caroline de Paula; Ramos, José Gustavo Venâncio da Silva; Carneiro, Charles; de Souza, Cláudio Leite; Possetti, Gustavo Rafael Collere; Aisse, Miguel Mansur (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2025)
Anaerobic technology is widely used in Brazil for the treatment of domestic sewage, due to favorable conditions such as a hot climate and lower operational costs. In this process, by-products such as biogas are formed, which can be recovered and converted into energy. Accordingly, the present study aimed to report the correlations between biogas production—both in gaseous and dissolved forms—and domestic sewage parameters, using full-scale modified UASB-type reactors installed in Curitiba, Paraná. Measurements were performed in real time over five months. The monitored influent and effluent parameters included pH, temperature, alkalinity, acidity, TSS, VSS, FSS, COD, sulfate, dissolved methane, and flow rate. Biogas parameters included flow rate and the concentrations of methane, carbon dioxide, and hydrogen sulfide. To assess the relationships between variables in the gaseous and liquid phases, Spearman’s correlation tests were applied. Operational results showed low removal efficiencies for BOD, COD, and TSS, attributed to the open design of the three-phase separator in this type of reactor. Most of the correlations between influent and effluent sewage parameters and biogas flow were moderate and positive, indicating that as biogas flow increased or decreased, these parameters tended to follow the same trend. However, correlations between sewage parameters and dissolved methane concentrations were weak or statistically non-significant, suggesting the need for further studies to better understand the influencing factors behind this relevant but often overlooked methane fraction.